2007
DOI: 10.1038/sj.bjp.0707414
|View full text |Cite
|
Sign up to set email alerts
|

Roscovitine, a cyclin‐dependent kinase inhibitor, affects several gating mechanisms to inhibit cardiac L‐type (Ca(V)1.2) calcium channels

Abstract: Background and purpose: L-type calcium channels (Ca (V) 1.2) play an important role in cardiac contraction. Roscovitine, a cyclin-dependent kinase inhibitor and promising anticancer drug, has been shown to affect Ca (V) 1.2 by inhibiting current amplitude and slowing activation. This research investigates the mechanism by which roscovitine inhibits Ca (V) 1.2 channels. Experimental approach: Ca (V) 1.2 channels were transfected into HEK 293 cells, using the calcium phosphate precipitation method, and currents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
76
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 45 publications
6
76
1
Order By: Relevance
“…These two effects were characterized by approximately equal EC 50 values (ϳ30 M), which suggested a single binding site. However, the Hill coefficient for (R)-roscovitine-induced slowed activation was ϳ1, whereas that for enhanced inactivation was Ͼ2, which could result from multiple binding sites (19). Intracellularly applied (R)-roscovitine failed to affect L-channel activity, which supported an extracellularly exposed binding site(s) mediating both effects.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…These two effects were characterized by approximately equal EC 50 values (ϳ30 M), which suggested a single binding site. However, the Hill coefficient for (R)-roscovitine-induced slowed activation was ϳ1, whereas that for enhanced inactivation was Ͼ2, which could result from multiple binding sites (19). Intracellularly applied (R)-roscovitine failed to affect L-channel activity, which supported an extracellularly exposed binding site(s) mediating both effects.…”
mentioning
confidence: 86%
“…The external recording solution contained 30 mM BaCl 2 , 100 mM NMG-Cl, 10 mM NMG-HEPES, osmolarity of 300 mosM, and pH 7.3. We used Ba 2ϩ as the permeant ion to exclude Ca 2ϩ -dependent inactivation (25,26), since we have previously demonstrated that (R)-roscovitine enhances VDI but does not affect calciumdependent inactivation (19). Both (R)-and (S)-roscovitine were prepared as a 50 mM stock solution in DMSO and stored at Ϫ30°C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations